Does SNORD116 mediate aspects of psychosis in Prader-Willi syndrome? Evidence from a non-clinical population. (April 2020) - Salminen, Iiro; Read, Silven; Hurd, Pete; Crespi, Bernard
Highlights: Prader-Willi syndrome shows high rates of psychosis and can be caused by SNORD116 deletions. SNPs & haplotypes in SNORD116 were linked with differences in paranoia among typical females. Three unlinked, imprinted loci at 15q11-q13 have now been associated with paranoia. Abstract: The paternally expressed gene SNORD116 encodes a set of short nucleolar RNAs that affect the expression of hundreds of other genes via epigenetic interactions. Lack of expression for SNORD116 has been implicated in major phenotypes of Prader-Willi Syndrome (PWS). Rates of psychosis and autism spectrum disorders are greatly increased in PWS, but the genetic and epigenetic causes of these increases remain unknown. We genotyped a large population of typical individuals for five SNPs within SNORD116 and phenotyped them for variation in schizotypal and autism spectrum traits. SNORD116 SNP and haplotype variation mediated variation exclusively in the Schizotypal Personality Questionnaire - Ideas of Reference subscale, which reflects variation in aspects of paranoia. The effect was restricted to females. SNORD116 represents, in addition to UBE3A and NDN-MAGEL2, a third, independent locus in the 15q11-q13 imprinted region that preferentially or exclusively affects levels of paranoia. This convergent pattern may reflect a common neural pathway affected by multiple genes, or an effect of interactions between the imprinted loci.